Inhibition of the hexosamine biosynthesis pathway potentiates cisplatin cytotoxicity by decreasing BiP expression in non–small‐cell lung cancer cells. Issue 6 (6th March 2019) - Chen, Wenshu; Do, Kieu C.; Saxton, Bryanna; Leng, Shuguang; Filipczak, Piotr; Tessema, Mathewos; Belinsky, Steven A.; Lin, Yong
Abstract: Platinum anticancer agents are essential components in chemotherapeutic regimens for non–small‐cell lung cancer (NSCLC) patients ineligible for targeted therapy. However, platinum‐based regimens have reached a plateau of therapeutic efficacy; therefore, it is critical to implement novel approaches for improvement. The hexosamine biosynthesis pathway (HBP), which produces amino‐sugar N ‐acetyl‐glucosamine for protein glycosylation, is important for protein function and cell survival. Here we show a beneficial effect by the combination of cisplatin with HBP inhibition. Expression of glutamine:fructose‐6‐phosphate amidotransferase (GFAT), the rate‐limiting enzyme of HBP, was increased in NSCLC cell lines and tissues. Pharmacological inhibition of GFAT activity or knockdown of GFATimpaired cell proliferation and exerted synergistic or additive cytotoxicity to the cells treated with cisplatin. Mechanistically, GFAT positively regulated the expression of binding immunoglobulin protein (BiP; also known as glucose‐regulated protein 78, GRP78), an endoplasmic reticulum chaperone involved in unfolded protein response (UPR). Suppressing GFAT activity resulted in downregulation of BiP that activated inositol‐requiring enzyme 1α, a sensor protein of UPR, and exacerbated cisplatin‐induced cell apoptosis. These data identify GFAT‐mediated HBP as a target for improving platinum‐based chemotherapy for NSCLC.